1991
DOI: 10.1093/ndt/6.10.683
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Dysfunction in Nephrotic Syndrome: Incidence and Prognostic Implications

Abstract: Although some cases of tubular dysfunction (TD) associated with nephrotic syndrome have been described, the incidence and the characteristics of this complication remain unknown. We investigated the presence of TD (renal glycosuria, aminoaciduria, metabolic acidosis with normal anion gap, hypouricaemia, and throughout hypophosphataemia) in 36 patients with nephrotic syndrome. Ten patients (group 1) showed glycosuria at some time during the course of their illness, ranging from 2.5 to 11.2 g/24 h. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Histological studies in the literature suggest the association of glycosuria with focal glomerulosclerosis, particularly in children (2,3). In our adult population we found various histological lesions in glycosuric patients and membranous glomerulonephritis was the most common form, in agreement with previously reported data (1). Other histological forms were focal glomerulosclerosis (5 cases), membranoproliferative glomerulonephritis (3 cases), mesangial IgA glomerulonephritis (1 case), and minimal change nephropathy (2 cases).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Histological studies in the literature suggest the association of glycosuria with focal glomerulosclerosis, particularly in children (2,3). In our adult population we found various histological lesions in glycosuric patients and membranous glomerulonephritis was the most common form, in agreement with previously reported data (1). Other histological forms were focal glomerulosclerosis (5 cases), membranoproliferative glomerulonephritis (3 cases), mesangial IgA glomerulonephritis (1 case), and minimal change nephropathy (2 cases).…”
Section: Discussionsupporting
confidence: 91%
“…Several causes have been proposed to justify tubular dysfunction with glycosuria in these patients. Praga et al (1) suggested a possible role of renal vein thrombosis in these patients but rejected this possibility because the patients showed no clinical-laboratory signs of the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tubular proteinuria is present in idiopathic nephrotic syndrome [1][2][3]. Tubular proteinuria includes markers of tubular damage and dysfunction such as N-acetyl-β-Dglucosaminidase (NAG) and retinol-binding protein (RBP), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…S4A). One of the key tasks of the proximal tubule is the reabsorption of metabolites, such as amino acids, and disruption of this function results in aminoaciduria, which is occasionally observed in nephrotic patients (22,23). Quantitative analysis (Wt1het vs wildtype) revealed that the amino acid carriers SLC3A1, SLC13A3 and SLC6A20a/b were decreased in single Wt1het mouse proximal tubules ( Fig.…”
Section: Resultsmentioning
confidence: 94%